Treatment of Colonial Mine Labourers at Mijnbouw Maatschappij Redjang Lebong (1928-1936) - Anjelina, Vina; Setiawati, Nur Aini (Diakronika, 2024)
This study highlights labour dynamics and socio-economic conditions at the Mijnbouw Maatschappij Redjang-Lebong (MMRL) gold mine in the late 1920s to 1930s. This research aims to analyze the treatment of labourers in the most significant gold and silver mining in the Dutch East Indies, MMRL. The method used in this research is the historical method with the research steps of heuristics, source criticism, interpretation, and historiography. The result shows fluctuations in the number of labourers and budget allocations for labour wages, explosives and other necessities from 1928 to 1936. Daily labourers significantly declined from 979 in December 1929 to 744 in December 1930. Differences in payment systems and benefits for contract, casual, and day labourers are also described, reflecting variations in wages and health facilities received. Occupational injuries and work-related illnesses were a common problem, with many labourers sustaining severe injuries as a result of the mine’s non-stop operations. MMRL provides medical facilities and implements health measures, but there remains a high risk of respiratory illness and other injuries. The excellent relationship between company owner H.J.A. Sanders and the labourers is also an essential factor in the social life of the labourers